Quantum algebraic symmetries in nuclear physics - Bonatsos, D.; Dascaloyannis, C. (HNPS Advances in Nuclear Physics, 2019)
The pairing correlations in a single-j nuclear shell are considered. It is proven that a simple boson mapping in terms of q-defonned bosons exists, which reproduces correctly both the commutation relations and the energy up to first order corrections, the parameter q being connected to the size of the shell. An exact solution in terms of a generalized deformed oscillator is also found